Two new species and synopsis of Chusquea subg. Platonia (Poaceae: Bambusoideae: Chusqueinae) in Bolivia and a new record for Peru - Guerreiro, Carolina; Alegria Olivera, Juan Jose; Rugolo De Agrasar, Zulma; Beck, Stephan; Vega, Andrea (Phytotaxa, 2014)
The present study describes and illustrates two new species of Chusquea subg. Platonia, C. parodii and C. paucispiculata. Chusquea laegaardii is cited for the first time in Bolivia and C. asymmetrica for Peru. Two keys for the identification of the species, mainly based on vegetative or reproductive characters, and a comparative table with micromorphological diagnostic features of foliage leaf blades are included. Finally, some remarks about the characteristics of the phytogeographical regions and the ecology of these new species are given.